Gambaran Visus Mata Pasca Pembelajaran Daring pada Anak Sekolah - Agustiningrum, Ratna; Pangestu, Bangkit; Kusumaningrum, Puput Risti; Permatasari, Devi (TRIAGE Jurnal Ilmu Keperawatan, 2024)
Pandemic Covid-19 has been spreading continuously since March 2020 in Indonesia. Online learning has been used as a solution to reduce the spread of the Covid-19 pandemic. However, the habit of frequently using smartphones during online learning for school-age children can disrupt eye health and lead to a decrease in visual acuity. Visual acuity abnormalities in school-age children's vision become a significant problem that needs immediate detection as early as possible so as not to affect the child's focus during the learning process. To understand the post-online learning visual perception of elementary school children. The research design employs a quantitative descriptive research method with a cross-sectional approach. The study population consists of students in grades 4, 5, and 6 at SDN 2 Sukorejo, totaling 43 respondents. The sampling technique used total sampling with exclusion criteria, resulting in a total of 38 respondents. Data analysis is conducted using frequency distribution. The characteristics of the elementary school children who were respondents had an average age of 11.18 years, with a minimum age of 10 years and a maximum of 13 years. The majority of respondents were female, totaling 21 children (55.3%). The results of this study revealed that the visual acuity of the right eye was normal in 33 children (86.8%), and the visual acuity of the left eye was normal in 36 children (94.7%). The post-online learning visual perception of elementary school children at SDN 2 Sukorejo mostly indicated normal vision.